Brief Prompting to Improve Classroom Behavior: A First-Pass Intervention Option. (January 2019) - Moore, Tara C.; Alpers, Andrew J.; Rhyne, Rachael; Coleman, Mari Beth; Gordon, Jason R.; Daniels, Stephanie; Skinner, Christopher H.; Park, Yujeong
Two studies were conducted to examine the effects of a brief prompting intervention (verbal and visual reminder of classroom rules) to improve classroom behavior for an elementary student during small-group reading instruction in a special education classroom (Study 1) and for three high school students with mild disabilities in an inclusive general education classroom (Study 2). Using within-participant reversal designs, the teachers provided brief reminders of behavioral expectations just before class. Teachers were instructed to respond to the students' appropriate and inappropriate behaviors in a typical manner to ensure no programmed changes in the contingencies for student behavior. Results indicated improvements in classroom behavior for all four students, and teachers and students indicated positive perceptions about the intervention and its effects. Implications for future research and practice are discussed.